Evaluation of Seed Grading Effect on Germination and Seedling Vigour of Diploknema butyracea (Butter Tree) - NAWA BAHAR; PREETI SHARMA (Seed Research, 2026)
Diploknema butyracea (Roxb.) H.J. Lam. is a fast growing, multipurpose tree species with several uses. Overviews of this species reveal that no work has been carried out on seed grading for production of quality seedling. Sowing of ungraded seed of a species gives rise to non-uniform planting material, which in turn gives rise to heterogeneity in the vigour and the size of the seedling produced. Hence, the present study was conducted with the objective to determine best dimension of seed for quality seedling production of butter tree.